2020
DOI: 10.24843/jpsa.2020.v02.i02.p05
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF METHANOL CONCENTRATION AS A SOLVENT ON TOTAL PHENOLIC AND FLAVONOID CONTENT OF BELUNTAS LEAF EXTRACT (Pulchea indica L.)

Abstract: Background: Beluntas (Pluchea indica L.) is an Indonesian plant that grows wild and is used as traditional medicine. Beluntas leaves are reported to contain phenolic, and flavonoid is a part of phenolic compounds. Phenolic compounds other than flavonoids include 1,3,4,5-tetra-O-caffeoylquinic acid, 3,4,5-tri-O-caffeoylquinic acid, chlorogenic acid, and ferulic acid. Flavonoid compounds in beluntas leaves are quercetin, apigenin, luteolin and chrysoeriol. Methanol solvents are reported to be able to extract hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 2 publications
0
7
0
4
Order By: Relevance
“…Flavonoids are polar compounds that can dissolve into other polar solvents such as ethanol, methanol, butanol, acetone, dimethylformamide, and others [19]. In some studies, organic solvents such as methanol were shown to dissolve flavonoids more effectively than other solvents [20,21].…”
Section: Discussion Phytochemical Active Content Analysis Resultsmentioning
confidence: 99%
“…Flavonoids are polar compounds that can dissolve into other polar solvents such as ethanol, methanol, butanol, acetone, dimethylformamide, and others [19]. In some studies, organic solvents such as methanol were shown to dissolve flavonoids more effectively than other solvents [20,21].…”
Section: Discussion Phytochemical Active Content Analysis Resultsmentioning
confidence: 99%
“…Pelarut yang memiliki sifat polar hanya dapat mengikat senyawa fitokimia yang juga bersifat polar, sedangkan pelarut yang bersifat non-polar hanya akan berikatan dengan senyawa yang juga bersifat nonpolar. (Mahasuari et al, 2020) bersifat semi-polar juga dapat berikatan dengan senyawa semi-polar hingga non-polar. Pelarut etil asetat diketahui memiliki sifat semi polar, sedangkan pelarut heksan diketahui bersifat non-polar.…”
Section: Pembahasanunclassified
“…Hasil akhir dari ekstrak kental biji gayam yang diperoleh dibandingkan dengan berat serbuk sebelum dilakukan proses ekstraksi dikalikan 100%.2.3 Pengujian golongan senyawa [10][11][12].…”
Section: Perhitungan Rendemanunclassified